A physiologia como método Epicúreo de investigação dos elementos imperceptíveis (Ádela) - Silva, Marcos Roberto Damásio da (2019)
This research looks into the theme of physiología in Epicurus thought, focusing on the investigation of imperceptible elements (ádela) whichcomprise the whole of reality, namely, atoms and void. The research is based on the canonical postulates elucidated in Criteriology, or systematic understanding of "criteria of truth" (kritéria tès aletheías). However, the epicurean investigation into reality, ergo an onto-gnosiology, stands on the sense-perceptions (aístheseis) as the fundamental and inalienable criterion to establish what is real and makes use of diánoia and psyche as the agents of data of possible knowledge, i.e. the articulation of instances of all which can be known. By means of the analogy via inference method of aesthetic universe, this work will demonstrate the legitimacy of the atomic speech which is not to be equated with an aesthetic order, thereforeit is deeper and more refined. Thus, this research employs aninvestigation method that is not as concerned with the phenomena, i.e. what appears (phainomenon), as with the first elements (stoicheia) from which the phenomena are constituted, i.e.set in motion only by reasoning (logoi) in the very activity of thepsyche and understanding (diánoia), which can be called the second navigation in the Epicurus philosophy